2018
DOI: 10.1093/annweh/wxy068
|View full text |Cite
|
Sign up to set email alerts
|

Respiratory Health Outcomes, Rhinitis, and Eczema in Workers from Grain Storage Facilities in Costa Rica

Abstract: High exposure to inhalable dust in Costa Rican grain storage facilities was associated to asthma symptoms and eczema in workers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 39 publications
0
8
0
Order By: Relevance
“…In the second phase, the texts of the remaining 80 publications were reviewed in full and, out of these, 58 were not eligible for inclusion. At the end, 22 publications 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 comprised this review according to the inclusion and exclusion criteria of the study. Of these, 12 had data that could be analyzed statistically, 17 , 18 , 23 , 24 , 27 , 33 , 36 , 38 as listed in Table 1 , Table 2 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the second phase, the texts of the remaining 80 publications were reviewed in full and, out of these, 58 were not eligible for inclusion. At the end, 22 publications 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 comprised this review according to the inclusion and exclusion criteria of the study. Of these, 12 had data that could be analyzed statistically, 17 , 18 , 23 , 24 , 27 , 33 , 36 , 38 as listed in Table 1 , Table 2 .…”
Section: Resultsmentioning
confidence: 99%
“… Exposure to particles less than 10 μm in diameter (PM10) American Thoracic Society's Division of Lung Disease (ATS-DLD-78 questionnaire) Respiratory symptoms and diagnosis of respiratory alteration. Toxicological medical assessment Goméz, M., 2009 32 (Argentina) Adolescents - students aged 13–14 years 23 schools in Salta, Argentina Personal and parental smoking ISAAC Questionnaire Current asthma or rhinitis Graudenz, G. S., 2002 33 (Brazil) Office workers Three different office buildings, located in the downtown area of São Paulo, in the same block and belonging to the same banking company Microbiological Assessment and dust A combination of two questionnaires: the ATS-DLD-78,20,21 and ISAAC Prevalence of respiratory symptoms among a group of office workers in São Paulo Herrera, R., 2017 34 (Chile) Chilean children living close to the mines Estimating the Causal Impact of Proximity to Gold and Copper Mines TSP (total suspended particulate) and PM10 pollution. ISAAC Questionnaire Asthma or allergic rhinoconjunctivitis.…”
Section: Resultsmentioning
confidence: 99%
“…A short version of the European Community Respiratory Health Study II questionnaire [45] was administered to study participants to identify respiratory symptoms (eg, wheezing, shortness of breath, coughing, and phlegm), respiratory diseases (eg, asthma and chronic bronchitis), allergic outcomes (eg, rhinitis and eczema), and common respiratory hazards such as smoking and pet ownership [46]. This questionnaire has been previously used in studies of Costa Rican populations [47-49].…”
Section: Methodsmentioning
confidence: 99%
“…A 2017 study of 136 Costa Rican grain production workers found that, within these grain storage facilities, there were elevated levels of inhalable dust concentrations (111). Such exposure has also been shown to be associated with incidence of asthma and eczema (112).…”
Section: Other Biological Threatsmentioning
confidence: 99%
“…The United States has not offered congressionally supported amnesty to undocumented immigrants since the 1990s [under the Departments of Commerce, Justice, and State, the Judiciary, and Related Agencies Appropriations Act of 1998; Pub. L. [105][106][107][108][109][110][111][112][113][114][115][116][117][118][119]. The Deferred Action for Childhood Arrivals (DACA) policy of 2012 offered some protections to undocumented immigrants brought to the United States as children.…”
Section: Fear Of Deportationmentioning
confidence: 99%